(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
After the dismemberment of the “Arab Homeland” by “Sykes – Picot Agreement” (1916), “Belford Declaration” (1917), the Independence of the “Orient States” (1946), and the establishment of the so-called “State of Israel” (1948), the concern of the USA was concentrated on rallying the States of the Middle East in a “Defense Organization” to resist the Arab National Orientation, and the ‘Communist Threats”, and to protect the western investments, through indigenous military forces and local self-finance. The USA and Western commitment towards this defense system is restricted to some military and technical assistance and full control of the military, economic, political, social and cultural activities in a way that protects and guarantees the western interests, investments and plans. بعد أن تكرست تجزئة الوطن العربي باتفاقية "سايكس بيكو" (1916)، و "وعد بلفور" (1917)، واستقلال "دول المشرق" (1946)، بناء على خطوط التجزئة والاستيلاء والفصل، وقيام ما يسمى بدولة "إسرائيل" (1948)، كان هم الولايات المتحدة حشد دول "الشرق الأوسط" في منظومة دفاعية تقاوم التوجه القومي العربي والتهديد الشيوعي، وتحمي الاستثمارات الغربية، بجيوش محلية وتمويل ذاتي، حيث تقتصر التزامات الغرب ببعض المساعدات العسكرية والفنية، مع السيطرة التامة على النشاط العسكري والاقتصادي والسياسي والاجتماعي والثقافي في المنطقة، بما يضمن مصالح الغرب واستثماراته ومخططاته.